Implementation of think-pair-share to mathematics instruction - Benidiktus Tanujaya; Jeinne Mumu (Intelektual Pustaka Media Utama, 2019)
The purpose of this research was to study the procedure of think pair share, the type of cooperative learning models, which can be implemented in mathematics instruction in Manokwari, West Papua Indonesia. This study was conducted at Senior High School in Manokwari (SMA Negeri 1), Manokwari West Papua Indonesia. The research was carried out using research and development methods. The Think Pair Share learning model was modified to get the procedure of implementation in accordance with the characteristics of students studying mathematics in Manokwari, West Papua. The results of the research showed that there were two principals in the application of the think pair share model in mathematics instruction in Manokwari West Papua, selection of group members and the determination of the number of group members. Students individually start thinking of finding answers to the assignment submitted. Group members must consist of students who already know each other well, but should not to have a similar level of knowledge, while the number of group members must start from two students.